2020
DOI: 10.1103/physreva.102.031301
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of ultracold atom-ion excitation exchange

Abstract: Ultracold atom-ion collisions are an emerging field of research that can ultimately lead to their precise quantum control. In collisions in which the ion is prepared in an excited state, previous studies showed that the dominant reaction pathway was charge exchange. Here, we explored the outcome products and the energy released from a single ultracold collision between a single 88 Sr + ion and a single 87 Rb atom prepared in excited metastable and ground electronic states, respectively, with control over their… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…To demonstrate our method, we measured the energy dependence of a non-adiabatic quench of a metastable electronically excited level of the ion during a collision with a ground-state atom . In previous work [36], we found that the excited long-lived 4d 2 D 5/2 and 4d 2 D 3/2 states of the 88 Sr + ion, quench after roughly three Langevin collisions with ground-state 87 Rb atoms, and that the excitation energy is transformed into kinetic energy of the colliding particles.…”
Section: Energy Dependence Of Non-adiabatic Quench Of Meta-stable Exc...mentioning
confidence: 80%
See 3 more Smart Citations
“…To demonstrate our method, we measured the energy dependence of a non-adiabatic quench of a metastable electronically excited level of the ion during a collision with a ground-state atom . In previous work [36], we found that the excited long-lived 4d 2 D 5/2 and 4d 2 D 3/2 states of the 88 Sr + ion, quench after roughly three Langevin collisions with ground-state 87 Rb atoms, and that the excitation energy is transformed into kinetic energy of the colliding particles.…”
Section: Energy Dependence Of Non-adiabatic Quench Of Meta-stable Exc...mentioning
confidence: 80%
“…In Ref. [36] we identified two types of collisional quenching. One is the EEE where the ion relaxes to the ground S state and the atom is excited to the P state followed by energy release of ∼ 3000 K•k B .…”
Section: Energy Dependence Of Non-adiabatic Quench Of Meta-stable Exc...mentioning
confidence: 99%
See 2 more Smart Citations
“…For energy E k B × 1 mK, an ion-atom collision involves many partial waves , due to the strongly attractive long-range nature of their interaction [17], allowing a semiclassical description of the collision. Despite continuous progress regarding the precise control of the trapped ion motion, reaching the ultralow relative energy regime (E /k B ≈ 1 μK or lower) for ion-atom collisions is still challenging experimentally [4,6,[18][19][20]. At these energies, quantum effects emerge, as few partial waves contribute to the collision.…”
Section: Introductionmentioning
confidence: 99%